Dynamic transcriptome changes during adipose tissue energy expenditure reveal critical roles for long noncoding RNA regulators - Bai, Zhiqiang (2018)
Enhancing brown fat activity and promoting white fat browning are attractive therapeutic strategies for treating obesity and associated metabolic disorders. To provide a comprehensive picture of the gene regulatory network in these processes, we conducted a series of transcriptome studies by RNA sequencing (RNA-seq) and quantified the mRNA and long noncoding RNA (lncRNA) changes during white fat browning (chronic cold exposure, beta-adrenergic agonist treatment, and intense exercise) and brown fat activation or inactivation (acute cold exposure or thermoneutrality, respectively). mRNA–lncRNA coexpression networks revealed dynamically regulated lncRNAs to be largely embedded in nutrient and energy metabolism pathways. We identified a brown adipose tissue–enriched lncRNA, lncBATE10, that was governed by the cAMP-cAMP response element-binding protein (Creb) axis and required for a full brown fat differentiation and white fat browning program. Mechanistically, lncBATE10 can decoy Celf1 from Pgc1α, thereby protecting Pgc1α mRNA from repression by Celf1. Together, these studies provide a comprehensive data framework to interrogate the transcriptomic changes accompanying energy homeostasis transition in adipose tissue.